Fresno-Merced Counties Legal Services Board Meeting at Los Panchos Restaurant - Watkins, Howard::::::::: (1981)
Front row Paul Babwin, Eugenia Mitchell, Robert Haden, Simao Avila; Back row: Tom Keene, Al Kathka and attendee